Assessment Of The Levels Of Interleukin-4 In The Gingival Crevicular Fluid Of A Group Of Patients With Chronic Periodontitis And A Group Of Non-Periodontitis Subjects (Journal of Pharmaceutical Negative Results, 2023)
The symptoms of periodontitis include inflammation of the tissues that support teeth. Numerous investigations have discovered a connection between rheumatoid arthritis, low levels of anti-inflammatory cytokines, and periodontal disease. This study sought to determine whether there were any correlations between the levels of Interleukin-4 in gingival crevicular fluid from patients with and without chronic periodontitis and indices of disease severity. Material and Methods: An ELISA test was performed on gingival crevicular fluid samples collected from 88 subjects with chronic periodontitis (44) and non-periodontitis (44) for the determination of IL-4 levels. Results: In the non-periodontitis group, the mean IL-4 concentration was highest (0.3± 0.006 pg/mL), and the chronic periodontitis group had the lowest mean IL-4 concentration (0.02 ± 0.027pg/mL). Conclusion: In patients with periodontitis, IL-4 concentrations decreased as the disease progressed. It is proposed that IL-4 may play a significant role in the remission of or improvement of periodontal disease.